2013
DOI: 10.5480/11-574.1
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Competent Practice in a Pre-Licensure Baccalaureate Nursing Program in the United States: A Mixed-Methods Study

Abstract: These findings suggest teaching/learning strategies and curricular design issues that may lead to greater student and faculty member cultural understandings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…Overall, the results are consistent with other literature, which commonly reports high levels of transcultural competences acquisition with the use of similar education approaches (Gallagher and Polanin, 2015;Gebru and Willman, 2003;Loftin et al, 2013;Papadopoulos et al, 2016;Shattell et al, 2013). In this regard, a variety of models describing cultural competence's multiple dimensions it has become a focus of attention over the past several decades (Loftin et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Overall, the results are consistent with other literature, which commonly reports high levels of transcultural competences acquisition with the use of similar education approaches (Gallagher and Polanin, 2015;Gebru and Willman, 2003;Loftin et al, 2013;Papadopoulos et al, 2016;Shattell et al, 2013). In this regard, a variety of models describing cultural competence's multiple dimensions it has become a focus of attention over the past several decades (Loftin et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…In this regard, a variety of models describing cultural competence's multiple dimensions it has become a focus of attention over the past several decades (Loftin et al, 2013). Teaching and learning strategies about culturally competent practice in nursing educations are essential to ensure a culturally competent health care workforce (Shattell et al, 2013). In studies of cultural competence education in nursing, findings support that the addition of culturally competent content increases on culturally competence measures, as students gain experience during their education (Allen, 2010;Lampley et al, 2008;Majumdar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…10,15 In relation to multiple cases, a study conducted in the United States, examined a baccalaureate pre-licensure nursing program at a public university. 12 In the field of nursing care, the case study method has been used in different areas, such as the health of the elderly, 20,23,26,43 home care and palliative care, 24 oncology, 25,41 women and child health, 28,36,38 surgical patients, 19,21 mental health, 39 and adverse events in care. 37 According to the produced evidence, the method has contributed to the improvement of care practices when investigating nursing care from the perspective of patients, 20 Families 40 and professionals.…”
Section: Discussionmentioning
confidence: 99%
“…This review revealed that the the case study application method in nursing research covered the different fields of activity of the profession, in particular education, care / care and administration / management. 6 In the field of nursing education, the selected studies addressed the evaluation of new teaching methodologies, 13 the analysis of technological teaching tools, 9-10,14-15 pedagogical practices, [7][8][11][12] and the ethical dimension in the training of nurses. [16][17] In addition to these, other areas can be deepened by the case study method, with research focused on educational policies, school and intermediate management, climate, culture and leadership, supervision, continuous and specialized training, teacher satisfaction, professional identity, curriculum, didactic and pedagogical practices, educational projects, teaching-learning models and strategies, and evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The obligation to train future nurses who can attend to the healthcare needs of different clients is paramount. It is essential that nursing programs and nurse educators heed the call for the groundwork of nurturing student nurses to become effective professionals, socially responsible citizens, who recognized the need to incorporate professional values and behaviors into their nursing care (Mixer, Lasater, Jenkins, Burk, Oliver, Meyer, Cruz, & Mills, 2013;;Shattell, Nemitz, Crosson, Zackeru, Starr, Hu, & Gonzales, 2013). It is the utmost desire of the researcher to bridge the gap brought about by the dearth of researches on cultural competence here in the Philippines.…”
Section: Introductionmentioning
confidence: 99%